Antifreeze Protein Supplementation During the Warming of Vitrified Bovine Ovarian Tissue Can Improve the Ovarian Tissue Quality After Xenotransplantation - Kong, Hyun Sun; Hong, Yeon Hee; Lee, Jaewang; Youm, Hye Won; Lee, Jung Ryeol; Suh, Chang Suk; Kim, Seok Hyun (Frontiers in Endocrinology, 2021)
The occurrence of ice crystallization during ovarian tissue (OT) cryopreservation causes unavoidable cryodamage, and ice recrystallization during the warming is more detrimental than ice crystallization. Here, we investigated that antifreeze protein (AFP) treatment during the warming procedure can improve the bovine OT quality after xenotransplantation (XT). Bovine OTs (n=120) were evenly assigned to four groups: fresh, vitrified-warmed, vitrified-warmed with 10 mg/mL Leucosporidium ice-binding protein (LeIBP, a type of AFP) (LeIBP-10), and vitrified-warmed with 20 mg/mL LeIBP (LeiBP-20). LeIBPs were added to the first warming solution. Twenty pieces of OTs were assigned to each category. The remaining 10 OTs from each category were assigned to the XT-Fresh control, XT-Vitrified-warmed control, XT-LeIBP-10, and XT-LeIBP-20 groups, respectively, and xenotransplanted to 9-week-old ovariectomized nude mice for one week. LeIBP treatment during the warming step increased morphological follicle normality and decreased apoptotic follicle ratios after vitrification-warming and XT. The XT-vitrified-warmed control group showed significantly reduced microvessel density and increased fibrosis when compared to that of the XT-fresh group. Microvessel density and fibrosis were recovered in both LeIBP treated groups. There was no significant difference between the LeIBP-10 and LeIBP-20 groups in all outcomes. AFP treatment during the warming procedure can prevent OT damage, and improve ovarian follicle morphology and apoptosis in both the vitrified-warmed bovine OT and its graft. After confirmation in a human study, AFPs can potentially be applied to human OT cryopreservation to reduce cryodamage and improve the OT quality.